Narrative and elucidating the concept of democracy: the case of Myanmar's activists and democratic leaders. Issue 2 (17th February 2019) - Wells, Tamas
ABSTRACT: Narrative analysis has been widely employed in the social sciences. Yet there has been no systematic application of narrative theory to the study of how the word "democracy" is given meaning by political actors. Using the empirical example of the Burmese democracy movement in the lead up to the historic 2015 election victory of the National League for Democracy, this article argues that narrative analysis can contribute in unique ways to the interpretive task of "elucidating" the concept of democracy. Tracing plot and character construction within activist and aid worker stories about democracy in Myanmar, this study reveals three prominent and diverging narratives of democracy within and around the movement; a liberal narrative, centring on liberal democratic institutions and values, a benevolence narrative, focussing on the value of moral leadership and selflessness, and an equality narrative, highlighting the importance of cultural reform towards greater relational equality. Attention to these narratives has implications for donor "democracy promotion" strategies raising new questions about the role of formal institutions of democracy, the perceived source of "solutions", and the impact on internal struggles within democracy movements.